Investigations on stability and performance of a varia-ble frequency based fuzzy logic controller for induction cooking system - Vishnuram, Pradeep; Nagarajan, Booma; Sureshkumar, A. (International Journal of Engineering and Technology, 2017)
Load variability and perturbation is an important issue in the induction cooking applications as it hinders the performance of the heating system considerably .Therefore a precise power control technique is required for induction heating applications by considering the stability issues and dynamic response of the system. Also, the safety operating ranges need to be confirmed to ascertain the competency of the controller. In this paper, a Fuzzy logic based power control scheme is introduced by considering the load uncertainties. The suggested power control technique uses variable frequency control of the inverter for reaching the target power level. Also, a detailed stability study is done for investigating stability range within which the system operation is safe and stable. The said work is simulated in MATLAB/Simulink environment and realized as a prototype where advanced FPGA controller renders its hand .The simulation and hardware results reveal that the suggested technique is versatile.